Efektivitas Terapi Latihan pada Pasien Parkinson dengan Barthel Index Skor - Salma Maha Rhani; Nuniek Nugraheni; Novira Widajanti (Sarana Ilmu Indonesia (salnesia), 2021)
Parkinson’s disease is the second most neurodegenerative disease after Alzheimer. This disease attacks approximately 1% of total world population. The proportion of the elderly population (?60 years) in Indonesia is increasing. This increase has a consequence, as a result of the decline in bodily functions causing increasingly the number of degenerative diseases in this age group. Until now, there has been no definitive treatment that can cure this disease thoroughly. Despite optimal medical treatment and neurosurgical intervention, people with Parkinson still experience progressive disability. The role of rehabilitation to maximize motoric and cognitive abilities as well as independence was suggested to improve the quality of life. This study aimed to determine the effectiveness of the exercise therapy in handling of Parkinson's patients in medical rehabilitation installation of RSUD Dr. Soetomo evaluated with Barthel Index. This research was a retrospective-analytic with a cross-sectional study design. The number of subjects was 24 with the criteria Parkinson patients who undergo exercise therapy for 3 months, had comorbid degenerative diseases, and did routine therapy twice a week. Subjects who met the criteria are interviewed using the Barthel Index questionnaire as an instrument. Statistical analysis was done with Wilcoxon-Signed Rank Test. P value of ? 0.05 was considered statistically significant. There was significant result of the effectiveness of exercise therapy in Parkinson's patients at the Medical Rehabilitation Installation at RSUD Dr . Soetomo (p=0,001). Exercise therapy is effective in treating Parkinson's patients at the Medical Rehabilitation Installation at RSUD Dr. Soetomo.